Strategic Deployment Of Knowledge Workers: A Case Study - Roy, Santanu; Ranjan, Jayanthi (Journal of Knowledge Management Practice, 2012)
In India, scientific and technological research being carried out in the government sector is concentrated primarily within the laboratories under the Council of Scientific and Industrial Research (CSIR), the primary umbrella for such laboratories. Planning and decisionmaking at the corporate level of CSIR, therefore, necessitates organizing information regarding the structure and functioning of the knowledge workers, the scientific personnel working in the laboratories of CSIR. These knowledge workers are strategic assets for CSIR, more so because of the tacit knowledge they possess as a result of actively pursuing R&D activities in different functional areas over long periods of time. The present study investigates into the structure and functioning of scientific personnel in CSIR. It analyzes the specific functions carried out by this set of knowledge workers across the various laboratories of CSIR in order to know the internal strengths and weaknesses of individual laboratories in different functional areas. For analyzing such categorical data, the methodology of correspondence analysis has been used. Using this methodology, the structure of multivariate relationships among the different CSIR laboratories in terms of the functions performed by the scientific personnel in these laboratories has been explored.